Mutualism with aggressive wood-degrading Flavodon ambrosius (Polyporales) facilitates niche expansion and communal social structure in Ambrosiophilus ambrosia beetles. (October 2016) - Kasson, Matthew T.; Wickert, Kristen L.; Stauder, Cameron M.; Macias, Angie M.; Berger, Matthew C.; Simmons, D. Rabern; Short, Dylan P.G.; DeVallance, David B.; Hulcr, Jiri
Abstract: Most wood-boring insects compete with wood decaying basidiomycetes for woody biomass. One clade of ambrosia beetles gained access to rotten wood – an abundant resource unsuitable to most wood-boring insects – by evolving a farming-like mutualism with a white rot polypore. Here we show the mutualist of Ambrosiodmus / Ambrosiophilus, the polypore Flavodon ambrosius, is superior in lignocellulolytic capacity compared to Ascomycota ambrosia fungi and other white rot Basidiomycota. This mutualism facilitated the evolution of large, long-lived, communal colonies with overlapping generations and egg-laying by pre-dispersal progeny females. F. ambrosius resembles other white rot Polyporales in that it causes significant weight loss in wood decay assays and strong polyphenol oxidase reactions, indicative of lignin-modifying enzymes. The symbiosis is asymmetrical: there are many species of Ambrosiodmus and Ambrosiophilus but all use a single known species of Flavodon, which determines the ecological strategy of the entire insect clade. Highlights: Fungus-farming mutualism discovered between Ambrosiophilus and Flavodon ambrosius. Flavodon ambrosius is a white rot fungus able to degrade lignin and cellulose. Communal behavior within multi-generational colonies and egg-laying by F1 females.